2008
DOI: 10.1111/j.1600-0404.2007.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cervicogenic headache: Vågå study of headache epidemiology

Abstract: CEH may be one of the three large, recurrent headaches. In this series, there was no female preponderance. Nuchal onset of pain is a characteristic trait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
118
3
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 19 publications
5
118
3
8
Order By: Relevance
“…as 4.1% in the general population (Sjaastad and Bakketeig 2008), is due to misdiagnosed migraine or TTH (Pöllmann et al 1997;Leone et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…as 4.1% in the general population (Sjaastad and Bakketeig 2008), is due to misdiagnosed migraine or TTH (Pöllmann et al 1997;Leone et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…The main cause of CGH is dysfunction in the upper cervical spine, and the mechanism of headache involves nociceptive structures such as the disks, upper cervical spinal nerves, facet joints, ganglia, muscles, and ligaments [3]. The prevalence of CGH in global population is 2.5-4.1% out of which females are more prone to this disease as the male to female ratio is 1:4 [4,5]. CGH represents a major health problem with tenderness and low quality of life [8].…”
Section: Introductionmentioning
confidence: 99%
“…Dry needling has grown in popularity and it is a relatively unique part of physical therapy practice. Number of studies has suggested that dry needling is a very effective technique to manage the musculoskeletal disorder [5][6][7]. Several studies also support that mulligan's C1-C2 sustained natural apophyseal glides (SNAGs) are a useful technique to reduce pain and improving range of motion [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CEH in the general population ranges from 0.7 to 17.8%, depending on the diagnostic criteria. [21][22][23][24] Using Dutch longitudinal physical therapy data (n = 9346) from 2009, the prevalence of CEH was estimated to be 0.95%.…”
Section: Introductionmentioning
confidence: 99%